A fuzzy–based cross–layer mechanism to improve the quality of video transmission over wireless LANs. (31st October 2014) - Ahmadian, Tahere; Nassiri, Mohammad
Providing Quality of Service (QoS) for multimedia applications over wireless networks is quite challenging. Enhanced Distributed Channel Access (EDCA) mechanism of IEEE802.11e standard is an attempt to improve QoS in these networks. With EDCA, high priority traffic has a higher chance of being sent. However, because of the variable and dynamic nature of wireless channel, the static scheduling mechanism used by EDCA to map arriving packets to various access categories (AC) does not provide multimedia users with desired level of QoS. In this paper, we propose a new cross–layer mechanism that relies on dynamic mapping of video as well as non–video packets to different access categories. Our approach exploits a fuzzy controller to assign video/data packets to different ACs according to traffic type and queue size of each AC. Simulation results show that our fuzzy–based approach outperforms existing mechanisms in terms of average PSNR, end–to–end delay, and packet delivery ratio.